2018
DOI: 10.1139/cgj-2017-0559
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prototype for modelling soil–pipe interaction and its application for predicting uplift resistance to buried pipe movements in sand

Abstract: This paper presents a testing rig for measuring the reactions on rigid pipes buried in sand during episodes of relative displacement. Following a detailed presentation of the 1g prototype, the test preparation procedure, and the characterization of the test sand’s shear strength and dilation potential under the low confining stresses pertinent to the problem, the paper focuses on the workflow devised to obtain accurate measurements of friction and arching effects, and accordingly normalize them to account for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The results obtained using eq 47 and 48 are shown in Figure 11. The results are also compared with the result obtained using DNV RP-F110 [62] and experimental means. It is observed that Equations (47) and (48) overestimate the uplift resistance in comparison to experimental results.…”
Section: Analytical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained using eq 47 and 48 are shown in Figure 11. The results are also compared with the result obtained using DNV RP-F110 [62] and experimental means. It is observed that Equations (47) and (48) overestimate the uplift resistance in comparison to experimental results.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…Several authors observed that soil strength is one of the crucial factors to influence the uplift resistance. They empirically or theoretically developed different models to predict the uplift resistance from undrained or drained soil resistance [62,63]. Thus, according to DNV RP F110 [64], the expression for uplift resistance was given as:…”
Section: Analytical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the simulation, the nonlinear spring (soil spring) with damper was used to simulate the coupling between the pipe and soil. [9][10][11][12][13] By setting the spring stiffness and damping coefficient, the soil supporting the pipeline can be simulated. In order to facilitate the analysis and calculation, following assumptions were made in this study:…”
Section: Contact Settingmentioning
confidence: 99%
“…This method is not only generally used to detect the reliability of product structure but also used for structural damage detection. 11,19 In the simulation, the sweep range was taken as 1-300 Hz. The sweep rate was set to 1 Hz and the value of excitation force was 0.3 N in this simulation, as shown in Figure 5.…”
Section: Parameter Setting Of Dynamic Analysismentioning
confidence: 99%